Maternal roles of Filipina mother-domestic workers in Metro Manila - Evaristo, Monique Denise A.; Saamong, Charla Rochella S.; Serrano, Katrina Andrea R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
This qualitative study aimed to determine how Filipina mother-domestic workers take on their maternal roles. It aimed to identify their perceived maternal roles and the actual maternal roles they perform. Twenty Filipina mother-domestic workers who were employed in Metro Manila were interviewed to gather detailed stories of their actual experiences in balancing family life and domestic work. The data gathered was analyzed using open coding and examined using the Symbolic Interaction Theory. From these, several themes under perceived and actual maternal roles were revealed. Results revealed that motherhood is perceived as a collective embodiment of providing for basic needs, being physically present, and instilling discipline. Meanwhile, similar themes emerged in relation to the actual maternal roles that the mother-domestic workers perform. These were identified as providing financial support, monitoring from afar, and giving emotional support. Such themes redefined the reproductive role of mothers as nurturers and caregivers into the more productive role as providers of the family. Overall, Filipina mother-domestic workers take on their maternal roles in varied ways for as long as the needs of their children are met. Specifically, nurturance is conveyed through financial support, parental guidance is made through the use of technology, and physical absence is compensated for through rare moments of quality time.
submitted
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman
Keywords: Working mothers -- Philippines -- Metro Manila; Mother and child -- Philippines -- Metro Manila; Household employees -- Philippines -- Metro Manila; Children of working mothers -- Philippines -- Metro Manila